2002
DOI: 10.1177/0146167202282001
|View full text |Cite
|
Sign up to set email alerts
|

I Belong, therefore, I Exist: Ingroup Identification, Ingroup Entitativity, and Ingroup Bias

Abstract: Merging insights from the intergroup relations literature and terror management theory, the authors conducted an experiment in which they assessed the impact of death-related thoughts on a series of ingroup measures. Participants in the mortalitysalience condition displayed stronger ingroup identification, perceived greater ingroup entitativity, and scored higher on ingroup bias measures. Also, perceived ingroup entitativity as well as ingroup identification mediated the effect of the mortality salience manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
356
3
16

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 435 publications
(398 citation statements)
references
References 44 publications
23
356
3
16
Order By: Relevance
“…Additionally, previous TMT research has shown that intergroup bias increases after individuals are reminded of their mortality (Greenberg, et al, 2001;Castano, et al, 2002;Nelson, et al, 1997).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, previous TMT research has shown that intergroup bias increases after individuals are reminded of their mortality (Greenberg, et al, 2001;Castano, et al, 2002;Nelson, et al, 1997).…”
Section: Resultsmentioning
confidence: 98%
“…Participants were more likely to blame a Japanese car maker than an American car maker for a vehicle crash after the MS condition, and were more likely to blame the company if it was a Japanese company than they were to blame the driver (Nelson et al, 1997). After MS, Italians were more likely to have a negative view of Germans (Castano et al, 2002), men were less receptive to pro-women courses at a university (Fritsche, & Jonas, 2005), younger people were more likely to distance themselves from older people (Martens, Greenberg, Schimel, & Landau, 2004), and participants were more likely to show bias in a minimal group setting (HarmonJones, Greenberg, Solomon, & Simon, 1996). The MS condition has also shown that…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…To assess participants' perceived similarity with the athlete, we adapted the in-group bias measure of Castano, Yzerbyt, Paladino, and Sacchi (2002). participants indicated on 7-point scales (1 = not at all, 7 = very much) to what degree six personal characteristics (Bsporty,^Binterested,^Bbalanced,B likeable,^Bmotivated,^Bopen^) apply to themselves similarly as to the athlete.…”
Section: Methodsmentioning
confidence: 99%
“…As research has shown, in times of terror people are known not to be open to out-groups. Instead, they prefer their in-group (see e.g., Baldwin & Wesley, 1996;Castano, Yzerbyt, Paladino, & Sacchi, 2002;Florian & Mikulincer, 1998). This suggests that it is likely that a messenger's message will be discarded when this message is counter-attitudinal.…”
Section: Persuasion Through the Use Of Mixed Attitudinal Messagesmentioning
confidence: 99%